Vegetation Analysis of Wetland Ecosystems in Southern Turkey Using the Fuzzy Means Method - Deniz Boz (Biology, 2025)
In this study, the vegetation of the natural area of the Göksu Delta Special Environmental Protection Agency (SEPA), one of Turkey’s most important wetlands, is researched. The importance of this study in terms of contributing to environmental protection and land use planning studies reveals that this natural area, where rare ecosystems are found, has started to degrade and disappear under human influence. This study was conducted because the area is not only a designated RAMSAR wetland (a wetland site designated of international importance especially for the Waterfowl Habitat under the Ramsar Convention) but also includes nearby residential developments. With this study, the vegetation of the area was studied to determine the syntaxonomic units across different habitats. The natural area of Göksu Delta is divided into three main habitat groups: aquatic, sand dune, and halophytic. In the research, the Braun-Blanquet method was used. During the research in the Göksu Delta, 279 sample areas were surveyed. The data were analysed according to the fuzzy means cluster method. During the investigation, 29 associations were identified, and 16 of them are considered a new finding for science. These 29 associations can be classified as follows: aquatic vegetation is represented with four associations (three of them belong to Phragmito-Magnocaricetea and one of them belongs to Potametea classes), sand dune vegetation is represented with 12 associations (belonging to Ammophiletea Br.-Bl. & Tüxen ex Westhoff, Dijk, & Passchier 1946 class), and halophytic vegetation is represented with 13 associations (six of them belong to Salicornietea fruticosae Br.-Bl. & Tüxen ex A. & O. Bolòs 1950, six of them belong to Juncetea maritimi Br.-Bl. in Br.-Bl., Roussine & Nègre 1952, and one of them belong to Molinio-Juncetea Br.-Bl. (1931) 1947 classes). Three (Onopordum boissieri, Ambrosia maritima, and Chlamydophora tridentata) of the endemics and rare plants that were explored during the study were recorded as new alliance characteristics.